Branched polymer-incorporated multi-layered heterostructured photoanode: precisely tuning directional charge transfer toward solar water oxidation. Issue 1 (6th December 2019) - Wei, Zhi-Quan; Dai, Xiao-Cheng; Hou, Shuo; Li, Yu-Bing; Huang, Ming-Hui; Li, Tao; Xu, Shuai; Xiao, Fang-Xing
Abstract : Two unidirectional electron and hole transfer channels were simultaneously constructed in a multilayered heterostructured photoanode via an efficient layer-by-layer assembly for solar-driven water oxidation. Abstract : Unidirectional and smooth charge transfer to the reactive sites plays an imperative role in boosting the solar-to-hydrogen conversion efficiency of photoelectrochemical (PEC) cells but suffers from sluggish charge transfer kinetics. Herein, as a proof-of-concept demonstration, high-speed spatially separated electron and hole transfer channels were simultaneously constructed in an integrated multilayered heterostructured photoanode via an efficient electrostatic layer-by-layer (LbL) assembly strategy, wherein a tailor-made positively charged polymer of branched polyethylenimine (BPEI) and negatively charged MoS2 quantum dot (QD) building blocks were intimately and alternately integrated on the hierarchically ordered TiO2 nanotube array (TNTA) framework in a unique "face-to-face" stacking fashion. The periodically alternately stacked ultra-thin BPEI layer in the ternary multilayered photoanode serves as a directional hole transport channel and the MoS2 QD layer functions as a cascade electron transfer channel, which synergistically contribute to the considerably enhanced separation and prolonged lifetime of charge carriers, endowing the multilayered TNTAs/(BPEI–MoS2 QDs) n photoanodes with markedly enhanced PEC water dissociation performances with respect to the single and binary counterparts under simulated solar light irradiation. Moreover, the essential role of the assembly unit was clarified. Our work would afford a new frontier to intelligently mediate the photoinduced charge flow by rationally constructing the unidirectional charge transport channels in semiconductor-based photoelectrodes for solar energy conversion.